Clinical and economic outcomes associated with respiratory syncytial virus vaccination in older adults in the United States. Issue 3 (24th January 2022) - Herring, William L.; Zhang, Yuanhui; Shinde, Vivek; Stoddard, Jeffrey; Talbird, Sandra E.; Rosen, Brian
Highlights: Respiratory Syncytial virus (RSV) can lead to hospitalization and death in older adults. Analyses of the potential economic value of investigational RSV vaccines are needed. A comprehensive economic model was developed and populated with current United States epidemiology data. RSV vaccination of older adults is likely cost-effective if priced similar to other older adult vaccines. Key economic value drivers are seasonal RSV incidence and hospitalization outcomes. Abstract: Background: Respiratory syncytial virus (RSV) is an important cause of lower respiratory infections and hospitalizations among older adults. We aimed to estimate the potential clinical benefits and economic value of RSV vaccination of older adults in the United States (US). Methods: We developed an economic model using a decision-tree framework to capture outcomes associated with RSV infections in US adults aged ≥ 60 years occurring during one RSV season for a hypothetical vaccine versus no vaccine. Two co–base-case epidemiology sources were selected from a targeted review of the US literature: a landmark study capturing all RSV infections and a contemporary study reporting medically attended RSV that also distinguishes mild from moderate-to-severe disease. Both base-case analyses used recent data on mortality risk in the year after RSV hospitalizations. Direct medical costs and quality-adjusted life-years (QALYs) lost per case were obtained from the literature and publicly available sources. Model outcomes included the population-level clinical and economic RSV disease burden among older adults, potential vaccine-avoidable disease burden, and the potential value-based price of a vaccine from a third-party payer perspective. Results: Our two base-case analyses estimated that a vaccine with 50% efficacy and coverage matching that of influenza vaccination would prevent 43, 700–81, 500 RSV hospitalizations and 8, 000–14, 900 RSV-attributable deaths per RSV season, resulting in 1, 800–3, 900 fewer QALYs lost and avoiding 557-1, 024 million. Value-based prices for the co–base-case analyses were 152-299 per vaccination at a willingness to pay of 100, 000/QALY gained. Sensitivity analyses found that the economic value of vaccination was most sensitive to RSV incidence and increased posthospitalization mortality risks. Conclusions: Despite variability and gaps in the epidemiology literature, this study highlights the potential value of RSV vaccination for older adults in the US. Our analysis provides contemporary estimates of the population-level RSV disease burden and insights into the economic value drivers for RSV vaccination.